The evolution of the cancer formulary review in Canada: Can centralization improve the use of economic evaluation?. (29th July 2016) - Wranik, W. Dominika; Gambold, Liesl; Hanson, Natasha; Levy, Adrian
Summary: Public reimbursement of drugs is a costly proposition for health care systems. Decisions to add drugs to the public formulary are often guided by review processes and committees. The evolution of the formulary review process in Canada's publicly funded health system is characterized by increased centralization and systematization. In the past, the review of evidence and recommendation was conducted at the regional level, but was replaced with the pan‐Canadian Oncology Drug Review in 2011. We assess the extent to which centralization and systematization of the review process have responded to past challenges, focusing on the use of economic evaluation in the process. Past challenges with economic evaluation experienced by regionalized review committees were identified from literature and qualitative data collected in the province of Nova Scotia. We categorize these using a typology with a macro‐, meso, and micro‐level hierarchy, which provides a useful framework for understanding at which level change is required, and who has the authority to influence change. Using grounded theory methods, we identify approaches used by Nova Scotia past committee members to compensate for perceived shortcomings of the process. These include an undue reliance on other committee members, on the multidisciplinarity of the committee, and on past decisions. Using a policy analysis approach, we argue that centralization and systematization of the review process only partially address the shortcomings of the previous regionalized process. Lessons from Canada can inform policy discussions across all health systems, where similar challenges with the formulary review process have been identified. © 2016 The Authors. The International Journal of Health Planning and Management published by John Wiley & Sons Ltd.